Analysis of the behaviour of the Tukad Buluk Poh flood water at the Gilimanuk - Denpasar National Road Crossing - Hidayat Acep; Suprapti; Isradi Muhammad; Dwi Praptoyo Riska (BIO Web of Conferences)
In most of Indonesia, floods are a common natural disaster that spreads into several watersheds during the rainy season. When river water outflow increases to the point where it overflows and floods the surrounding area, this is known as a flood. Over the past few years, there has been an increasing number of flood incidents throughout the rainy season, which has resulted in significant losses for those impacted by this calamity. One of the rivers in Bali’s Jembrana district is Tukad Biluk Poh. It has a watershed area of around 84 km2, is about 28 km long, flows into the Indian Ocean, and is one of the rivers that floods the most. Access to Gilimanuk to Denpasar via the national road was not immune to the flood overflow at the time in Tukad Biluk Poh. To prevent flooding on this portion of the road, this study aimed to ascertain the flood water level on the Gilimanuk-Denpasar National Road bridge that crosses Tukad Biluk Poh. When the flood discharge was analyzed using the Nakayasu method’s synthetic unit hydrograph, the design flood discharge had return periods of 299,720 m/sec for two years, 436,764 m3/sec for five years, 529,525 m3/sec for ten years, 648,435 m3/sec for twenty-five years, and 1134,737 for a thousand years. The HEC-RAS tool was then used for a hydraulic analysis to ascertain the flood water level, and the findings were excellent. For two years, MAB yields 1.78m, for five years, 2.31m; for ten years, 2.64m; and twenty-five years, 2.64m. 3.03 years, with MAB returning 3.34 years, 1 MAB returning 3.51 years, MAB returning 5.76 years, and MAB returning 6.21 years. The bridge is referred to as the current one by obtaining the flood water level at the 200th year return period of the bridge’s condition, which is 4.65 meters on the pavement and 3.10 meters on the bottom of the girder at the design flood water level. Based on the analysis, the bridge’s height was raised to 7.71 meters at the base of the top structure, considering a 1000-year design flood and a 1.50-meter guard height.